RNA and imidazoquinolines are sensed by distinct TLR7/8 ectodomain sites resulting in functionally disparate signaling events. - Colak, E; Leslie, A; Zausmer, K; Khatamzas, E; Kubarenko, A; Pichulik, T; Klimosch, SN; Mayer, A; Siggs, O; Hector, A; Fischer, R; Klesser, B; et al. (2014)
TLRs 7 and 8 are pattern recognition receptors controlling antiviral host defense or autoimmune diseases. Apart from foreign and host RNA, synthetic RNA oligoribonucleotides (ORN) or small molecules of the imidazoquinoline family activate TLR7 and 8 and are being developed as therapeutic agonists. The structure-function relationships for RNA ORN and imidazoquinoline sensing and consequent downstream signaling by human TLR7 and TLR8 are unknown. Proteome- and genome-wide analyses in primary human monocyte-derived dendritic cells here showed that TLR8 sensing of RNA ORN versus imidazoquinoline translates to ligand-specific differential phosphorylation and transcriptional events. In addition, TLR7 and 8 ectodomains were found to discriminate between RNA ORN and imidazoquinolines by overlapping and nonoverlapping recognition sites to which murine loss-of-function mutations and human naturally occurring hyporesponsive polymorphisms map. Our data suggest TLR7 and TLR8 can signal in two different "modes" depending on the class of ligand. Considering RNA ORN and imidazoquinolines have been regarded as functionally interchangeable, our study highlights important functional incongruities whose understanding will be important for developing TLR7 or 8 therapeutics with desirable effector and safety profiles for in vivo application.